Penetapan Vitamin C dalam Jeruk Keprok Segar dan Jus secara Iodometri: Determination of Vitamin C in Fresh Tangerines and Juice by Iodometry - Qurrotu A’yunin Lathifah; Dora Dayu Rahma Turista; Andyanita Hanif Hermawati; Riska Miftakhul Jannah (Borneo Journal of Medical Laboratory Technology, 2022)
Orange has high levels of Vitamin C. The most frequently consumed orange is tangerine. People usually consume fresh oranges and juice. This study aimed to determine the difference in Vitamin C content in fresh tangerine and tangerine juice. The research design used was experimental. Population in this study area includes all citrus fruits sold in the Ngemplak Tulungagung market. The sample was obtained by using the purposive sampling technique. The data obtained are fresh tangerine has a content of Vitamin C as much as 26,4% and tangerine juice as much as 7,2%, then data is processed with the software SPSS 16 and analyzed by Independent T-test. Result of Independent T-test is obtained P-value = 0.001 < α = 0.05.Based on the result of the Independent T-test, it can be concluded that H0 is rejected, so there is a difference in Vitamin C content in fresh tangerine and tangerine juice on an Iodometric basis.